Current Therapeutic Approaches for Human Metapneumovirus Infections: Challenges and Opportunities - Neelam Singla (Asian Journal of Pharmaceutics (AJP), 2025)
Human metapneumovirus (hMPV) is a widely spread respiratory virus that mainly infects infants, older adults, and immunocompromised individuals with mild-to-severe respiratory disease. This review discusses the transmission, clinical presentations, current treatment methods, and diagnostic challenges associated with the hMPV. Due to the overlapping of symptoms with other respiratory viruses, such as respiratory syncytial virus and influenza, hMPV is frequently misdiagnosed, which adds to the difficulties of managing the disease. To date, no antiviral drugs or vaccines have been licensed for the treatment of hMPV, and supportive therapy remains the standard of care. Recent studies have focused on emerging therapeutic strategies, including nucleoside analogs, fusion inhibitors, monoclonal antibodies, and RNA interference-based treatments. Vaccine approaches, such as subunit protein vaccines, virus-like particles, and live attenuated vaccines, are also widely practical. The article also focuses on persistent challenges surrounding current treatments, including diagnostic constraints, immune evasion, and the need for enhanced surveillance to monitor viral evolution. Progress in molecular diagnostics and immunotherapy holds promise for future advances in hMPV control, underscoring the importance of ongoing research and global preparedness.